2023
DOI: 10.1038/s41467-023-41630-x
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacteria shape antimicrobial T-helper cell responses during infancy and adulthood

Katrin Vogel,
Aditya Arra,
Holger Lingel
et al.

Abstract: Microbial infections early in life are challenging for the unexperienced immune system. The SARS-CoV-2 pandemic again has highlighted that neonatal, infant, child, and adult T-helper(Th)-cells respond differently to infections, and requires further understanding. This study investigates anti-bacterial T-cell responses against Staphylococcus aureus aureus, Staphylococcus epidermidis and Bifidobacterium longum infantis in early stages of life and adults and shows age and pathogen-dependent mechanisms. Beside act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Vogel et al. showed that S. aureus enhanced a Th1 response, whereas Bifidobacterium , a classic infant-associated bacteria, had a mitigating effect on this immune response ( 64 ). HMOs are known to have a bifidogenic effect and can therefore indirectly support this microbiome-driven immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Vogel et al. showed that S. aureus enhanced a Th1 response, whereas Bifidobacterium , a classic infant-associated bacteria, had a mitigating effect on this immune response ( 64 ). HMOs are known to have a bifidogenic effect and can therefore indirectly support this microbiome-driven immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding practices are identified as central factors in influencing the structure of breast milk microbiota, as the microbiota in infant’s oral cavity reciprocally influence the microbial composition of breast milk by retrograde inoculation. In this process, microbes from the infant’s oral cavity are transferred to the breast during breastfeeding, subsequently colonizing the mammary gland, contributing to reshaping the breast milk microbiota. , In summary, these studies have provided insights into the characteristics and major factors influencing microbial communities in breast milk, which can have a significant impact on the health and growth of the infant, including immune system maturation and digestive function. ,, However, it is important to recognize that the diversity and evolutionary aspects of the microbial community in breast milk are complex and require further exploration. Current research primarily focuses on microbial taxonomy and abundance studies, while there is a need for a deeper understanding of their biological functions and interactions.…”
Section: The Microbial Community In Human Breast Milk and Its Dynamicsmentioning
confidence: 99%
“…Vogel and collaborators (2023) reported that the gut bifidobacteria population can shape antibacterial Th-cell responses during infancy. These bacteria can modulate T cells by inducing FoxP3+CD4+T cells, elevating IL-10 and galectin-1 secretion, and exerting CTLA-dependent suppression, thereby inhibiting Staphylococcus -specific Th cell activation through a cell-dependent mechanism . From breast milk to the infantile gut, bifidobacteria fortify infantile immune responses, providing an early immunological shield through intricate interactions with other microorganisms and host cells.…”
Section: Benefits Of Breast Milk Microbiota and Its Metabolites For I...mentioning
confidence: 99%
See 2 more Smart Citations